2022
DOI: 10.12659/msm.937928
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Treatment of Pediatric Tracheobronchial Foreign Bodies: A Retrospective Analysis of 715 Cases

Abstract: Background This study aimed to analyze the clinical characteristics of tracheobronchial foreign bodies in children in Shenzhen and to explore the diagnosis and treatment methods for special cases. Material/Methods This study included a total of 715 children who were diagnosed with tracheobronchial foreign bodies at Shenzhen Children’s Hospital between October 2016 and October 2021. Data on sex, age, inducement, symptoms, foreign body type, foreign body location, foreign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Another study conducted in China showed that the overall incidence of FBI was significantly higher among males (69.1%) [12], which reflects how gender is an influencing factor of FBI among the pediatric age group. This influence could be due to differences in physiological development, such as the development of mastication, laryngeal protection, and swallowing coordination [12]. However, the association between gender and FBI in our study was not statistically significant (p=0.19).…”
Section: Discussionmentioning
confidence: 95%
“…Another study conducted in China showed that the overall incidence of FBI was significantly higher among males (69.1%) [12], which reflects how gender is an influencing factor of FBI among the pediatric age group. This influence could be due to differences in physiological development, such as the development of mastication, laryngeal protection, and swallowing coordination [12]. However, the association between gender and FBI in our study was not statistically significant (p=0.19).…”
Section: Discussionmentioning
confidence: 95%
“…Foreign bodies of the upper airway often produce symptoms of obstruction, such as stridor, wheezing, chest retractions, and/or persistent cough, and should be suspected in patients who do not respond clinically to treatment for upper airway infection or upper airway reactive disease [ 4 ]. The diagnosis of an airway foreign body can be aided by fiberoptic bronchoscopy or a CT scan [ 5 ]. We describe a rare case of hair tourniquet syndrome of the uvula secondary to an upper airway foreign body.…”
Section: Introductionmentioning
confidence: 99%